2018
DOI: 10.3892/ol.2018.9292
|View full text |Cite
|
Sign up to set email alerts
|

Oct3/4 is potentially useful for the suppression of the proliferation and motility of hepatocellular carcinoma cells

Abstract: Hepatocellular carcinoma (HCC) cells are immature compared with healthy mature hepatocytes. Transcription factors serve a role in hepatocyte differentiation. The expression levels of transcription factors in HCC cell lines have been investigated to determine potential therapeutic targets. In the present study, the HLE, HLF, PLC/PRF/5, Huh-7, Hep3B, Huh-6 and HepG2 HCC cell lines were subjected to reverse-transcription polymerase chain reaction (RT-PCR) of transcription factors, including NANOG, Oct3/4, GATA bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The regulation of cell proliferation in HLF cells is modulated by different factors like Oct3/4. Indeed, the down-regulation of Oct3 /4 was demonstrated also to regulate proliferation and motility in HLF cells, but not in other hepatocarcinoma cell lines [37], increasing β-catenin protein level with a consequent Wnt signaling amplification, finally enhancing the invasive cellular activity that is characteristic of epithelial-mesenchymal transition [38]. Such features can reasonably explain the behavior in terms of silencing response of HLF compared to the other primary tumor cell lines investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of cell proliferation in HLF cells is modulated by different factors like Oct3/4. Indeed, the down-regulation of Oct3 /4 was demonstrated also to regulate proliferation and motility in HLF cells, but not in other hepatocarcinoma cell lines [37], increasing β-catenin protein level with a consequent Wnt signaling amplification, finally enhancing the invasive cellular activity that is characteristic of epithelial-mesenchymal transition [38]. Such features can reasonably explain the behavior in terms of silencing response of HLF compared to the other primary tumor cell lines investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was performed using renal cell lines. Although it has been reported that Oct3/4 knockdown suppressed the proliferation of hepatocellular carcinoma cells in the condition of 3-day incubation (Tomizawa et al, 2018), whether suppressed proliferation restore by longer incubation is remained to be unknown. In fact, in the present study, 3-day incubation of ACHN cells with LXR inverse agonist caused a decrease in cell number, however, the cell number was restored after 4 days (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Oct3/4 is also involved in cancer cell growth. For example, Oct3/4 knockdown suppresses the proliferation of hepatocellular carcinoma cells (Tomizawa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%